Pengembangan Kegiatan Belajar Mengajar Berbasis Digital Melalui Program Literasi Dan Numerasi Di SDN Srimukti 1 Tambun Utara - Cep Adiwiharja; Diah Wijayanti; Zahra Zahra; Hari Sugiarto; Melsa Rahmadania; Devina Brigitta Azahra; Firdaus Ibrahim (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This literacy and numeracy training and mentoring service activity is to prepare the nation's next generation to face challenges in the global era, where to produce selective education requires quality human resources, including the development of literacy and numeracy in learning at SDN Sri Mukti 01, North Tambun, use digital-based technology at SDN Sri Mukti 01 Tambun Utara and knowledge for teachers and parents and guardians regarding the use of digital-based technology in learning. Training and development methods are carried out offline or face-to-face by students through lecturer assistance which includes introducing the scope of literacy and numeracy learning, as well as supporting teachers in developing literacy and numeracy by utilizing digital-based technology in learning and teaching activities. It is hoped that with this training, SDN Sri Mukti 01 Tambun Utara students and teachers can develop digital-based learning and teaching activities for numeracy literacy